Proses Pengangkatan Anak dan Dampak Hukum pada Anak Setelah Diangkat terkait Perwalian dan Pewarisan: Studi Kasus di Kabupaten Klaten - Tristiana, Enis; Dwikowati, Francisca Vani (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This study investigates the issue, specifically the process of registering child adoption at the Population and Civil Registration Office of Klaten Regency, as well as the legal consequences of adopted children related to guardianship and inheritance after adoption. The research method employed is empirical research, descriptive research, a qualitative research approach, primary and secondary data sources, data collection techniques involving observation and interviews, and data analysis techniques involving reduction, presentation, and conclusion drawing. According to the findings of this study, the process of recording child adoption is divided into three stages: filing for adoption at the Social Service for Women's Empowerment, Child Protection, and Family Planning in Klaten Regency, determining the Islamic District or Religious Court, and finally recording child adoption at the Population and Population Service Office. Civil Registration in the Regency of Klaten. Meanwhile, it is concerned with the legal consequences of child adoption, such as guardianship and inheritance. The Civil Code and the Compilation of Islamic Law have different legal consequences after adoption. The legal consequences of adopting children in relation to guardianship and inheritance differ in the Civil Code (KUHPer) and the Compilation of Islamic Law (KHI). In the Civil Code, the civil relationship between biological parents and children is severed, whereas in the KHI, the opposite is true. Adopted children are heirs in the KUHPer, but not in the KHI, where mandatory will replace them. As a result, the family can determine the applicable law through a court order.